Effects of Water Deficit on Growth, Biomass Allocation and Photosynthesis of A. senegal Seedlings from Nguru and Gujba Provinces of Yobe State, North Eastern Nigeria - A.U. Jibo; M.G. Barker (Journal of Applied Sciences and Environmental Management)
Acacia senegal (L) Willd is a multipurpose tree species that occurs  throughout semi-arid Africa. Poor yields of gum from the species in the semi-arid region of Nigeria may be due to more frequent drought events. It is not yet clear whether some populations of A. senegal may respond  differently to any encroaching drought. The effects of water deficit on growth, biomass allocation and photosynthesis of A. senegal seedlings from Nguru and Gujba province of Yobe state, North Eastern Nigeria were studied under glasshouse conditions for 120 days. Plants were subjected to three watering regimes; control (well-watered) conditions corresponding to 25% gravimetric water content (GWC), mild water deficit at 15% (GWC) and severe-water-deficit at 10% (GWC), respectively. There was a highly significant difference in stomata conductance among the treatments (F2, 84=11.38, P< 0.001) in relation to water deficit. There was no statistical difference in quantum yield between the two provenances (F1, 84 =0.15, P=0.695) and interaction between treatment and provenances was also not significant (F2, 84= 2.14, P=0.124). mean root length between the provenances were significantly different (F2,84 =0.60, P< 0.001) however Root length was not statistically significant between treatments (F2,84= 0.60, P= 0.550). Plant biomass, stomata conductance, quantum yield, chlorophyll fluorescence, relative water content, root length and root: shoot ratios were highly responsive to changes in soil water. It was concluded that A. senegal is capable of physiological adjustment in response to soil moisture as a form of ecological adaptation.